THE NOMINALISM IN MONTAIGNE’S ESSAYS - F.R de Oliveira, Marcelo (Sapere Aude, 2020)
this paper faces the hard and almost unexplored issue on Montaigne’s nominalism. It also contains interesting clues about the skepticism in the Middle Ages. It shows the most important extracts of the Essays that would be written under the nominalism’s influence. Most of the scholars even ruminate on that Montaigne translated a Middle Ages’ work. This road certainly leads us to the very few explored issue about the relationships between the Essays and the later Scholastic. Working with an edition of Montaigne’s translation (1581) of Sebond’s Theologia, this paper presents extracts from Sebond’s nominalism that were on the root of some extracts of the Essays.